2002
DOI: 10.1159/000054948
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbamazepine on Dexamethasone Suppression and Sleep Electroencephalography in Borderline Personality Disorder

Abstract: The pathophysiology of borderline personality disorder (BPD) remains obscure, but there is mounting evidence of brain dysfunction without focal abnormality. The dexamethasone suppression test (DST) and sleep electroencephalography (sleep EEG) have been studied in BPD, but the findings seem to be related to a concomitant axis I diagnosis of major depression (MD) rather than to BPD itself. There is no effective treatment for BPD. Carbamazepine (CBZ) has shown contradictory results and in a previous study, our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…They found that BPD patients used a significantly higher percentage of both PRN and standing medications to help them sleep (Plante et al 2009), demonstrating again the clinical relevance of sleep disturbances in BPD, and suggesting a high risk of drug abuse due to these disturbances. De la Fuente et al (2002) found that carbamazepine (CBZ) increased slow wave sleep in the sleep EEG of BPD patients. CBZ was chosen because of its mood-stabilizing effect and its moderating effect on aggressive behaviour (Dalby 1975).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…They found that BPD patients used a significantly higher percentage of both PRN and standing medications to help them sleep (Plante et al 2009), demonstrating again the clinical relevance of sleep disturbances in BPD, and suggesting a high risk of drug abuse due to these disturbances. De la Fuente et al (2002) found that carbamazepine (CBZ) increased slow wave sleep in the sleep EEG of BPD patients. CBZ was chosen because of its mood-stabilizing effect and its moderating effect on aggressive behaviour (Dalby 1975).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…This kind of research approach holds promise to integrate endocrine and clinical approaches of BPD. Another study has investigated the effects of carbamazepin on HPA axis in BPD, which is not only used in the treatment of epilepsy but also of affective disorders, and found increased postdexamethasone plasma cortisol values [114]. However, the underlying mechanisms as well as the clinical benefit are still under discussion.…”
Section: Bpd: Psychopathology and Clinical Featuresmentioning
confidence: 99%
“…Seven studies were obtained concerning carbamazepine (CBZ), with the best evidence being a class II trial in borderline personality disorder 31 and the rest were all class III of evidence. This AED was primarily associated with a significative increase in SWS and a concomitant decrease in the REM stage in a class III study performed in healthy volunteers 32 .…”
Section: Resultsmentioning
confidence: 99%
“…This AED was primarily associated with a significative increase in SWS and a concomitant decrease in the REM stage in a class III study performed in healthy volunteers 32 . Subsequent trials confirmed this by using CBZ in acute treatment of patients with focal epilepsy 33,34 , in psychiatric disorders 31 , and in healthy volunteers 35 . In a smaller study, conducted in healthy individuals, CBZ also appeared to improve sleep continuity and efficiency 36 .…”
Section: Carbamazepinementioning
confidence: 89%